Valuation of Environmental Goods in Profit and Non-Profit Housing Sectors: Evidence from the Rental Market in the City of Zurich - Silvia Banfi; Massimo Filippini; Andrea Horehájová (Swiss Journal of Economics and Statistics, 2008)
This paper analyses the impact of electromagnetic pollution, noise and air pollution on the rent level for the aggregated and disaggregated market in the city of Zurich, Switzerland. Although there is no conclusive assessment about the health impacts of electromagnetic radiation people are nonetheless concerned about possible long term risks associated with the exposure. This risk perception may affect the price of dwellings located close to antenna. The regression results show that the environmental variables considered have the expected sign and are highly significant, with exception of the presence of an antenna and the air pollution for the non-profit submarket. However, the greatest part of the variation is explained by the structural variables.
Keywords: C21; Q2; R31; 330; hedonic pricing; electrosmog; noise; air pollution; market segmentation